Safety and Efficacy Evaluation of Ultrasound Aspirators in Intramedullary Spinal Cord Tumors Surgery: An Experimental Study on a Swine Model - Mauro Palmieri; Alessandro Pesce; Mattia Capobianco; Massimo Corsini; Giorgia Iovannitti; Fulvio Aloj; Giuseppa Zancana; Vincenzo Esposito; Maurizio Salvati; Antonio Santoro; Gianpaolo Cantore; Alessandro Frati (Brain Sciences, 2025)
Introduction: Intradural extramedullary and intramedullary spinal tumors are rare, complex to treat, and require advanced surgical techniques. Ultrasonic aspirators, commonly used for tumor removal, can cause sensory and motor deficits, including loss of motor evoked potentials (MEPs). This study aims to evaluate the safety and efficacy of ultrasonic aspirators in intramedullary tumor surgery using a swine model, comparing different systems and techniques. Methods: Ten pigs underwent D1-D3 laminectomy and myelotomy, with adipose tissue simulating a tumor. The ultrasonic aspirators were tested under varying conditions (fragmentation power, suction, application time, and vibration mode). The primary endpoint is to evaluate the impact of the chosen variables on motor function damage. The secondary endpoints are histological evaluation of the type of damage caused by ultrasound aspirators and the effect of steroid drugs on MEPs’ impairment recovery. Results: Ultrasound aspirators can cause a significant MEP signal reduction when used in continuous mode, with fragmentation power >30 for more than 2 min (p < 0.001). Suction does not affect MEPs. When used in alternating/pulsatile mode, fragmentation power and application time do not affect MEPs. The two-way ANOVA analysis on the interaction between fragmentation power and application time in continuous mode did not demonstrate a significant interaction (p = 0.155). Time alone does not affect motor damage (p = 0.873). Betamethasone can restore MEPs’ signal after damage if administered immediately. Conclusions: Using ultrasonic aspirators in an animal model of intramedullary tumor surgery is safe. The main factor that resulted in the responsibility of motor function impairment is the fragmentation power.